GCC Countries And Their Role In Activating Foreign Direct Investment The Kingdom Of Saudi Arabia As A Model (1985-2021) Imam Mohammed Ibn Saud Islamic University (IMSIU) - Al-Siddig Talha M. Rahma , Amir Mohammed Diab Ismail , Tawfig Eltayeb El Basher Abdelrahman , Dr. Durria Hyder Siddeg (Migration Letters, 2023)
The aims of this paper is to examine the determinants of foreign direct investment in Saudi Arabia over the period ((1985-2021). The dependent variable is foreign direct investment. The independent variables are inflation, GDP, government spending, economic openness, and exports. The Dickey-Fuller test is used to determine whether a unit root, a feature that can cause issues in statistical inference, is present in an autoregressive model. The result of the co-integration shows significant relationship between foreign direct investment and the independent variables. According to the results of the error correction model, all the variables have significantly effect on foreign investment in the long run. In the short, the study shows a significant correlation between GDP and FDI in the Saudi Arabia. The study recommends that the Kingdom of Saudi Arabia must make maximum efforts to attract FDI to promote its economy